The role of ethical behavior and entrepreneurial leadership to improve organizational performance - Anak Agung Dwi Widyani; Nengah Landra; Nengah Sudja; Mateus Ximenes; I Wayan Gde Sarmawa (Cogent Business & Management, 2020)
This study aims to examine the role of ethical behavior and entrepreneurial leadership in improving organizational performance. This research was conducted at the management of the Lembaga Perkreditan Desa (LPD) in Bali. Based on 2016 data, the number of LPDs in Bali was 1433 units, but 177 units were not operating, so 1256 units spread out in 9 districts/cities. Sampling is based on Slovin formula with 9% precision, so the number of LPDs sampled is 34 units. The determination of LPD samples in each district/city was carried out by stratified proportional random sampling. The research respondents were LPD administrators consisting of heads, secretaries, and treasurers in each LPD sample, so the number of respondents was 102 people. Data retrieval is done through interviews with respondents based on the prepared questionnaire. Furthermore, data processing is carried out with the SmartPLS 3.0 program. The results of the study found that ethical behavior is part of entrepreneurial leadership behavior. Ethical behavior can significantly improve LPD performance. Integrating ethical behavior with entrepreneurial leadership is significantly able to improve organizational performance (LPD), so ethical entrepreneurial leadership is very important in the management of the organization.
Keywords: 650; ethical behavior; entrepreneurial leadership; ethical entrepreneurial leadership; organizational performance